Liquid thermal conductivity of three biodiesel compounds: Methyl myristate, methyl laurate and methyl caprate. (April 2021) - Fan, Jing; Liu, Shuangshuo; Meng, Qinglong; Song, Fenhong
Highlights: Biodiesel is considered as an ideal choice of alternative fuel. Transport property is vital for its application. Thermal conductivity of three fatty acid esters was measured (pressure up to 15 MPa). Abstract: In order to provide the basic thermophysical property data for the research of alternative clean fuels, the liquid thermal conductivity of methyl myristate, methyl laurate and methyl caprate which are considered as the main compounds of biodiesel was reported. The measurements of three fatty acid esters, covering a temperature range from (292 to 372) K and pressure up to 15 MPa, have been performed by a transient hot-wire technique with a bare platinum hot wire. The relative uncertainty of the experimental results was estimated to be ± 2.0% (in the 0.95 confidence level). The present thermal conductivity data were correlated as a polynomial function of temperature and pressure for the purpose of interpolation.